2022
DOI: 10.9770/ird.2022.4.4(3)
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of entrepreneurial attitude among administrators of selected community colleges and universities in Leyte

Abstract: The school administrators adopted an "Entrepreneurial Attitude" approach to run the school profitably. Furthermore, administrators who embrace successful entrepreneur techniques were able to attain and establish an effective school, as the literature says. Using a descriptive survey method, this study determined the factors that affect the entrepreneurial attitudes of school administrators and faculty in selected universities and colleges in the 4th congressional district of Leyte through model generation. Hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Faith largely determines how people think, feel, motivate and behave, influences choices, perseverance in action, or effort put into achieving a goal. Self-efficacy is the foundation of motivation (Bandura, 1997;Agapito, Jala & Cruz-Español, 2022;Grencikova et al, 2022;Hutmanová et al, 2022;Samašonok, Juškevičienė, 2022).…”
Section: Coping With Stress: Styles Self-efficacy and Internal Confli...mentioning
confidence: 99%
“…Faith largely determines how people think, feel, motivate and behave, influences choices, perseverance in action, or effort put into achieving a goal. Self-efficacy is the foundation of motivation (Bandura, 1997;Agapito, Jala & Cruz-Español, 2022;Grencikova et al, 2022;Hutmanová et al, 2022;Samašonok, Juškevičienė, 2022).…”
Section: Coping With Stress: Styles Self-efficacy and Internal Confli...mentioning
confidence: 99%
“…Scientists carry out scientific research in universities. At the same time, understanding the attitude of scientists toward entrepreneurship in the university is critical but needs to be studied (Agapito et al, 2022). An analysis of the academic environment in four European countries found that academics in the natural sciences see their faculties as more entrepreneurially oriented than the social sciences (Kalar & Antoncic, 2015).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…The expansion of economies and businesses worldwide has meant that universities face the great challenge of adequately educating future professionals, as a digital and globalized world requires a more competitive and betterprepared workforce. This rapidly developing phenomenon is a multidimensional and multifactor process that affects all educational institutions and, in particular, the competitiveness of universities (Coroș et al, 2021;Agapito et al, 2022). By 2025, half of all jobs will be predicted to be filled by highly skilled workers (Bileviciute et al, 2019).…”
Section: Introductionmentioning
confidence: 99%